Venoms and Extracellular Vesicles: A New Frontier in Venom Biology - Auwal A. Bala; Naoual Oukkache; Elda E. Sanchez; Montamas Suntravat; Jacob A. Galan (Toxins)
Extracellular vesicles (EVs) are nanoparticle-sized vesicles secreted by nearly all cell types under normal physiological conditions. In toxicological research, EVs have emerged as a crucial link between public health and multi-omics approaches, offering insights into cellular responses to disease-causing injury agents such as environmental and biological toxins, contaminants, and drugs. Notably, EVs present a unique opportunity to deepen our understanding of the pathophysiology of envenomation by natural toxins. Recent advancements in isolating and purifying EV cargo, mass spectrometry techniques, and bioinformatics have positioned EVs as potential biomarkers that could elucidate biological signaling pathways and provide valuable information on the relationship between venomous toxins, their mechanisms of action, and the effectiveness of antivenoms. Additionally, EVs hold promise as proxies for various aspects of envenomation, including the toxin dosage, biological characterization, injury progression, and prognosis during therapeutic interventions. These aspects can be explored through multi-omics technology applied to EV contents from the plasma, saliva, or urine samples of envenomated individuals, offering a comprehensive integrative approach to understanding and managing envenomation cases.